A Phenomenological Case Study: The Construction of Digital Literacy in Early Childhood Within the Family - Coryza Nursyahbani; Muniroh Munawar; Dwi Prasetiyawati Diyah Hariyanti (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
This study aims to analyze the process of constructing digital literacy in young children within the family, identify the role of parents, and examine the factors influencing it. The study employs a qualitative approach with a phenomenological design involving 7 parents of children aged 4–6 years as informants. Data were collected through in-depth interviews,observations, and documentation, and were analyzed using the Miles and Huberman interactive model. The results indicate that children’s digital literacy is shaped through habitual technology use, the role of parents as mediators, and the process of behavioral modeling. Parents who actively guide their children tend to foster more purposeful technology use, while a lack of guidance leads children to become passive users. Additionally, social environmental factors and family conditions also influence this process. This study concludes that digital literacy in early childhood is the result of social construction within the family, not merely a consequence of access to technology. Therefore, active parental involvement, support from early childhood education institutions, and government policies are necessary to optimally foster children’s digital literacy.